Thermal Brownian motion and thermophoretic of reacting hybridized nanoparticles in Williamson-water base fluid with convective cooling cylinder - S.O. Salawu; A.M. Obalalu; E.O. Fatunmbi; O.Y. Oludoun (Hybrid Advances)
The valuable characteristics of copper and aluminium oxide nanoparticles in enhancing the thermal performance of industrial cooling processes have propelled the study. This will give insights into the long-term stability and economic feasibility of nanofluid viscous materials for cooling systems design and potential advancement of nanotechnology. As such, this analysis examines the thermal properties of hybridized Cu–Al2O3 nanoparticles dispersed in a convective cooling cylinder containing Williamson-water base solvent. The Williamson–Cauchy fluid model is adopted to represent the rheological complex behaviour of the base fluid adequately. A coupled impact of Brownian motion and thermophoresis are captured to prompt the dynamical interactions at the nanoscale, especially the phenomena influence on the overall heat propagation. A Galerkin-weighted residual technique is employed to solve the transformed invariant governing model, including the momentum, thermal, and reacting species equations. The study used a range of fluid terms to investigate their influences on a cylinder’s thermal distribution and cooling efficiency. The outcomes present that the hybridized Cu–Al2O3 nanoparticle substantially enhances the base fluid thermal conductivity, improving the convective heat transport rates. The Brownian motion encourages uniform temperature distribution, while thermophoretic forces support nanoparticles’ effective migration and thermal performance optimization. Also, the chemical reactions pivoted the modulation of temperature and concentration fields to influence the whole heat transfer characteristics.